Identificación de Necesidades para Proponer el Desarrollo Turístico en la Comunidad de Tuncarta, del Cantón Saraguro de la Provincia de Loja - Abrigo Córdova, Pablo Antonio (2016)
A high in the Andes in southern Ecuador,between the provinces of Azuay and Loja,lies the saraguro canton. Saraguros live there, look for an indigenous culture known for its well-preserved lifestyle,clothing and traditional crafts, quichua language and cuisine. The people Saraguro proudly maintain the cohesive cultural factors that have structured their life for hundreds of years. They have worked to preserve their indigenous identity from the spanishconquest and continue during modernization and actual globalization. Worldwide walkers will experience the proud community of Saraguro in his native town. In addition to the vibrant and rich culture, Saraguro also has great natural beauty,flora,fauna and Opportunity of the many adventure activities. Almost the entire tourism infrastructure is local, creating an authentic travel experience and Sustainable. One of the main problems facing the canton Saraguro and in particular the community Tuncarta, is the erosion of their land , due to lack of vegetation, especially in the high contradictory product of deforestation and forest fires has been; and lack of awareness for the care and preservation of primary forests. Another drawback identified in the area is the absence of an adequate system of tourism and environmental signage, something that hinders appreciation and characterization of the potential of the sector. Furthermore unknown mechanisms to develop sustainable tourism in place and care of natural resources. Referencing the aforementioned background, we believe are relevant evidence to present identification mechanisms of ailments that make the community Tuncarta not touristically developed (Rivero, 2010), for it was used in the research, ongoing training, implementation of the MDP, focus groups, discussion groups and seminars for residents of the community, whose results were evidenced in the short and long term, promoting in involved full awareness of protection, environmental care and awareness, andas a mature and comprehensive mindset developed through partnership and community work. Moreover, we believe that education is an axis of good living, because, in the educational process should include the preparation of future citizens for a democratic, fair, inclusive and peaceful society. By virtue of the beneficiaries of this project responsibilities exercised within the framework of multiculturalism, respect for diversity,and harmonious and respectful coexistence with nature (Sumak Kawsay). (SENPLADES, 2013).